The impact of carvacrol on the larval gut bacterial structure and function of Lymantria dispar - Yang, Jing; Chen, Yun-Ze; Zhang, Guo-Cai (Frontiers in Microbiology, 2024)
The gut bacteria of insects play an important role in regulating their metabolism, immune system and metabolizing pesticides. Our previous results indicate that carvacrol has certain gastric toxic activity on Lymantria dispar larvae and affects their detoxification metabolism at the mRNA level. However, the impact of carvacrol on the gut bacteria of L. dispar larvae has been unclear. In this study, the 16S rRNA sequencing technology was used to sequence and analyze the gut bacteria of the larvae which were exposed with sublethal concentration (0.297 mg / mL) and median lethal concentration (1.120 mg / mL), respectively. A total of 10 phyla, 16 classes, 47 orders, 72 families, 103 genera, and 135 species were obtained by using a 97% similarity cutoff level. The dominant bacterial phyla in the gut of the L. dispar larvae are Firmicutes and Proteobacteria. The treatment with carvacrol can significantly affect the structure of gut bacteria in the larvae of the L. dispar. At both doses, carvacrol can shift the dominant gut bacteria of the larvae from Proteobacteria to Firmicutes. At the genus level, two doses of carvacrol can significantly enhance the relative abundance of probiotic Lactobacillus in the gut of L. dispar larvae (P ≤ 0.01). Additionally, significant differences were observed among the five bacterial genera Burkholderia-Caballeronia-Paraburkholderia, Anoxybacillus, Pelomonas, Mesorhizobium (P ≤ 0.05). The analysis of αdiversity and β-diversity indicates that the treatment with carvacrol at two doses significantly affect the bacterial richness and diversity in the larvae. However, the results of functional classification prediction (PICRUSt) indicate that carvacrol significantly down-regulate 7 functions, including Energy metabolism, Cell growth and death, and up-regulate 2 functions, including Carbohydrate metabolism and Membrane transport. The network analysis indicates that the correlation between gut bacteria also has been changed. In addition, the insecticidal activity results of carvacrol against L. dispar larvae with gut bacteria elimination showed that gut bacteria can reduce the insecticidal activity of carvacrol against L. dispar larvae. This study provides a theoretical foundation for understanding the role of gut bacteria in detoxifying plant toxins and conferring pesticide resistance.